Being Real on Instagram Reels: An Authentic Tool to Enhance English Speaking Skills - Dewi, Ni Putu Purnama; Marsakawati, Ni Putu Era; Putra, I Nyoman Adi Jaya; Suwastini, Ni Komang Arie (Elsya : Journal of English Language Studies, 2022)
As technology rapidly develops new features, empirical testing of their capability to assist in educational purposes are always needed. This study takes a look at Instagram Reels, which is seldom explored as a language teaching tool, especially for vocational high school students. This study aims at describing students’ perceptions, challenges, and strategies in using Instagram reels as an authentic tool for improving speaking skills. The research used descriptive qualitative research methods. The subjects of the study were five eleventh-grade students from one of the public vocational high schools in Bali, Indonesia. They were selected by conducting a purposive sampling technique. The observation and interview were conducted to collect data. The findings show that a) the perceptions of students on the implementation of Instagram reels to improve speaking skills were favorable. Most students agreed that implementing Instagram reels as an authentic tool in speaking was adaptable, effective, and authentic. It also increased the students’ speaking abilities, which were referred to as positive attitudes. Instagram reels boosted students’ consciousness, motivation, and enhancing their vocabulary, grammar, pronunciation, accent, and cultural knowledge. b) Students faced a variety of challenges when using Instagram reels as a learning medium, such as limited internet access and a lack of digital literacy. To overcome the challenges, students used some strategies, namely using WIFI facilities at school or other public places, practicing a lot, and seeking additional information to improve digital literacy skills using Instagram reels.